2007
DOI: 10.1038/sj.mt.6300227
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Transgene Expression After Intrastriatal Pseudotyped rAAV2/1, rAAV2/2, rAAV2/5, and rAAV2/8 Transduction in the Rat

Abstract: In vivo recombinant adeno-associated viral vector (rAAV)-mediated transduction of various tissues including brain has been characterized by slow onset and gradual increase in gene expression before reaching stable long-term protein levels. The early time course of transgene expression has not been quantified using newly available rAAV capsid serotypes. In this experiment, the onset of expression of green fluorescent protein (GFP) after intrastriatal injection of rAAV2-based pseudotyped vectors (rAAV1, rAAV5, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 41 publications
10
99
2
Order By: Relevance
“…Our findings are in accordance with the results of several groups that have found that rAAV injections do not induce astrogliosis or infiltration of microglia into the brain [35][36][37] or to a very low extent. 38 The better performance of AAVs in terms of background contrast generation might be explained by the fact that AAV particles are not enveloped, and can therefore withstand more extensive concentration and purification procedures resulting in higher titer and purity. Owing to the higher expression levels combined with the reduced background contrast, AAV-mediated MRI reporter gene delivery to the rodent brain resulted in a better distinction between the contrast generated by the vector encoding for FerrH from a control vector injection (eGFP) and hence a better contrast to background.…”
Section: Evaluation Of Ferritin As Mri Reporter Gene G Vande Velde Et Almentioning
confidence: 99%
“…Our findings are in accordance with the results of several groups that have found that rAAV injections do not induce astrogliosis or infiltration of microglia into the brain [35][36][37] or to a very low extent. 38 The better performance of AAVs in terms of background contrast generation might be explained by the fact that AAV particles are not enveloped, and can therefore withstand more extensive concentration and purification procedures resulting in higher titer and purity. Owing to the higher expression levels combined with the reduced background contrast, AAV-mediated MRI reporter gene delivery to the rodent brain resulted in a better distinction between the contrast generated by the vector encoding for FerrH from a control vector injection (eGFP) and hence a better contrast to background.…”
Section: Evaluation Of Ferritin As Mri Reporter Gene G Vande Velde Et Almentioning
confidence: 99%
“…These findings are encouraging considering that intraparenchymal injections of therapeutically-relevant doses of rAAV have been shown to induce innate and adaptive immune responses in rodents and non-human primates. [18][19][20] Such immune responses lead to the elimination of transgeneexpressing cells and/or silencing of the transgene, and may account for the poor translation of gene therapy approaches observed in preclinical and clinical studies. 21 Indeed, eradication of rAAV2/2-transduced hepatocytes by cell-mediated immunity has been observed in a Phase I clinical trial for hemophilia.…”
mentioning
confidence: 99%
“…Only C57BL/6 mice of ~8 weeks old were used throughout this study. It has been also shown that viral expression of GFP in striatal neurons and astrocytes in rats could be detected 4 days post injection, reached a plateau by 2 -4 weeks post injection, and then remained stable for 9 months post injection 21 . The time course of cytoGCaMP3 expression has not been precisely determined here, but at least two weeks for virus expression are recommended.…”
Section: Discussionmentioning
confidence: 95%